The bishops of the Church of England in Canada and Newfoundland; being an illustrated historical sketch of the Church of England in Canada, as traced through her epsicopate. - Mockridge, Charles Henry, 1844-1913. (London, Church Bells, 1896)
Mode of access: Internet.